Novel Role of ER Stress and Autophagy in Microcystin-LR Induced Apoptosis in Chinese Hamster Ovary Cells - Zhang, Shenshen; Liu, Chuanrui; Li, Yang; Imam, Mustapha U.; Huang, Hui; Liu, Haohao; Xin, Yongjuan; Zhang, Huizhen (Frontiers in Physiology, 2016)
Microcystin-LR (MC-LR) is a ubiquitous peptide that exhibits strong reproductive toxicity, although the mechanistic basis for such toxicity remains largely unknown. The present study was conducted to investigate the mechanisms underlying the adverse effects of exposure to MC-LR in Chinese hamster ovary (CHO) cells. The results showed that MC-LR inhibited the in vitro proliferation of CHO cells significantly, with an IC50 of 10 μg/mL. Moreover, MC-LR-treated CHO cells revealed strong induction of cell cycle arrest and apoptosis. Additionally, exposure of CHO cells to MC-LR resulted in excess reactive oxygen species production and intracellular calcium release, with resultant endoplasmic reticulum stress (ERs). There was also extensive accumulation of autophagic vacuoles with the highest concentration of MC-LR used (10 μg/mL). Furthermore, the expression of ERs (GRP78, ATF-6, PERK, IRE1, CHOP) and autophagy (Beclin1 and LC3II) proteins was increased, with concomitantly reduced expression of LC3I suggesting that ERs and autophagy were induced in CHO cells by MC-LR treatment. Conversely, pretreatment of CHO cells with 4-Phenyl butyric acid, the ERs inhibitor reduced the MC-LR-induced apoptotic cell death and cellular autophagy as evidenced by the reduced expression of Beclin1 and LC3II. Similarly, MC-LR treatment in combination with an autophagy inhibitor (3-methyladenine) increased apoptotic cell death compared with MC-LR alone, and induced ERs via upregulating ERs proteins. The overall results indicated that activation of ERs and autophagy are both associated with MC-LR-induced apoptosis in CHO cells. ERs may be a trigger of autophagy in this process.